THE EFFECT OF USING THE TRAINING MODULE ON THE KNOWLEDGE LEVEL OF SMALL DENTIST CADRES - Nurul Fatikhah; Irwan Supriyanto; Sekar Restuning (Politeknik Kesehatan Kemenkes RI Jakarta I, 2023)
Background: Little dentists were selected elementary school students who become UKGS cadres to play an active role in implementing some health improvement efforts in their schools. UKGS activities run less than optimally due to the lack of involvement of small doctor cadres and very minimal knowledge about dental and oral health owned by small doctor cadres. The prevalence of dental caries in Indonesia is still high, namely 92,6% for the age group 5-9 years and 73,4% for the age group of 10-14 years. Therefore, it is necessary to carry out various innovations and breakthroughs to prevent caries, one of which is the small dentist training module innovation. The use of modules in health education has a positive impact on increasing knowledge. Modules were printed teaching materials that are designed to be studied independently by learning participants without being accompanied by a teacher. Objective: This study aims to analyze the effect of using the training module on the knowledge level of small dentist cadres. Methods: This type of research is a quasi-experimental design with Pre and Post with Control Group Design with a total sample of 30 people from each group. Results: The results of the influence analysis before and after training using the cadre training module using the Paired T-Test obtained ?-value = 0.000 (? <0.05), meaning that there is a significant change in the average knowledge score before and after training using the module small dentist cadre training. The difference in the value of knowledge after cadre training between the intervention group and the control group resulted in ?-value = 0.043 (?<0.05), which means that there was a significant difference between the intervention group and the control group.